(untitled) (Encuentros, 2021)
The aim of this research is to characterize the conceptions of future mathematics teachers when posing research questions within the framework of writing graduate work. Questionnaires were applied to 36 students enrolled in the last semesters of the mathematics undergraduate program and were analyzed based on a thematic analysis. The results indicate that the conceptions of future mathematics teachers refer to the research question as the means by which the problem under investigation is materialized, the main function is to guide the research from theoretical-methodological aspects, they recognize the need to carry out meaningful research questions that impact the educational context.